The potential detection of low-level aerosol isotopes from new civilian nuclear processes. (August 2017) - Miley, H.S.; Burnett, J.L.; Foxe, M.P.; Haas, D.A.; Keillor, M.E.; Lowrey, J.D.; Mayer, M.F.; McIntyre, J.I.; Wood, J.S.
Abstract: As the world faces a challenging future in maintaining the commercial availability of radioactive isotopes for medical use, new methods of medical isotope production are being pursued. Many of these are small in size and could effectively operate continuously. With the potential for much shorter retention times, a new suite of isotopes may soon be found in the environment. The authors estimate that many more aerosols containing low-level isotopes of gas/volatile origin could be detectable at short range and times, and a few at longer ranges and times as compared to those released in more common nuclear reactor operations. Highlights: New Medical Isotope production (MIP) facilities are coming online. Modeled novel and classical medical isotope production techniques. MDA values have been calculated for a multidimensional gamma-spectrometer. New MIP methods may result in the environmental detection of additional isotopes.